Application of waste catalyst, CaO-SiO2 in the transesterification of palm oil - Siti Norhafiza, Mohd Khazaai; Ting, Sih Yi; Mohd Hasbi, Ab. Rahim; Mohd Lokman, Ibrahim; Maniam, Gaanty Pragas (Universiti Kebangsaan Malaysia, 2021)
The increment of global demand for energy resources and peaking of atmospheric carbon dioxide level have gained researcher's attention to study the alternative energy from renewable resources. In this work, biodiesel were produced by utilizing waste catalysts in converting palm oil into biodiesel. The waste eggshell and sea sand (sources of calcium oxide (CaO) and silicon oxide (SiO2)) were used to produce CaO-SiO2 heterogeneous solid catalyst. The effects of different ratio of both sources of catalysts and reaction variables such as reaction time, methanol to palm oil ratio and catalyst loading were studied. Surprising, the analysis using FTIR showed similar functional groups detected before and after the calcination process. Thus, uncalcined SiO2 was chosen to assist the transesterification process. It was found that 93.01% biodiesel yield were produced at the optimal conditions studied: 65±3 C, 12: 1 methanol to oil ratio within 1 hour 30 minutes, and the application of 5 wt.% catalysts. In conclusion, the CaO-SiO2 heterogeneous solid catalyst derived from waste eggshell and sea sand showed high potential for biodiesel production from palm oil.